2015
DOI: 10.1002/anie.201501895
|View full text |Cite
|
Sign up to set email alerts
|

On‐Demand Ambient Ionization of Picoliter Samples Using Charge Pulses

Abstract: Relay electrospray ionization (rESI) from a capillary containing a sample solution (or from an array of such capillaries) is triggered by charge deposition onto the capillary. Suitable sources of primary ions, besides electrosprays, are plasma ion and piezoelectric discharge plasma sources. With no requirement for physical contact, high-throughput sample screening is enabled by rapidly addressing individual secondary (sample) capillaries. Sub-pL sample volumes can be loaded and sprayed. Polar analytes, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
65
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 44 publications
0
65
0
1
Order By: Relevance
“…The high voltage added in ESI might affect the low potential applied in the EC system. Li et al 30 have recently reported a new ionization method, in which a hand-triggered piezoelectric pistol was used to generate primary ion flow, and the ions could induce spray from the capillary tip end. This new ionization strategy has negligible influence on the EC system.…”
Section: Introductionmentioning
confidence: 99%
“…The high voltage added in ESI might affect the low potential applied in the EC system. Li et al 30 have recently reported a new ionization method, in which a hand-triggered piezoelectric pistol was used to generate primary ion flow, and the ions could induce spray from the capillary tip end. This new ionization strategy has negligible influence on the EC system.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al described a new technique called relay ESI, in which a PDD plasma was used as the primary ion source. This PDD plasma ionization method has been adapted here as an open‐air ionization technique.…”
Section: Introductionmentioning
confidence: 99%
“…V 10 mL) can undoubtedly impact the precision and efficiencyo fb iological investigations in drug-development and point-of-care (POC) diagnosis. [1][2][3][4] Facilitated by the improved sensitivity and specificity provided by modern mass spectrometry (MS) instrumentation, the replacement of traditional complex laboratory procedures with integrated miniaturized methods has become ag rowing trend in POC diagnosis. [5] In recent years,advances in direct sample to mass spectrometry techniques,s uch as paper-spray ionization, probe electrospray ionization, and touch spray [2,[5][6][7] have allowed for the application of these methods towards the quantitative analysis of small volumes of biofluids.However, the sensitivity and precision typically achieved in the laboratory through adequate sample preparation prior to the MS quantification is traded off.T herefore,techniques capable of isolating and enriching target analytes from complex matrices with minimal processing time and adequate sample clean-up are highly desirable for applications that require direct introduction to MS. [1-3, 8, 9] As ac oncept, solid-phase microextraction (SPME) embraces solventless microextraction technologies with different geometrical configurations that efficiently integrate sampling and sample clean-up,while also allowing for enrichment of the molar fraction of ag iven analyte in as ingle step.…”
mentioning
confidence: 99%
“…Certainly,the ability to perform rapid equilibration under static conditions can be beneficial for applications where agitation of the sample is not possible or cumbersome (e.g.a nalysis of tissue, [10] single cells, [17] and small samples [4] ). Ther apid rate of enrichment of analytes on the tip can be explained by radial diffusion (detailed discussion about radial diffusion and SPME devices is provided on the Supporting Information).…”
mentioning
confidence: 99%